Strengthening social protection in East Asia - Asher, Mukul G.; Kimura, Fukunari 1958- (Routledge-ERIA studies in development economics, 2015)
"There is considerable scope for examining pension and healthcare together as a social protection system, and for regressed analytical studies, focusing on specific major issues of relevance in strengthening social protection. This book aims to fill the literature gap on social protection in East Asia by covering issues such as: pension and health care arrangements in depopulating high income countries of Japan and Korea; the challenges of pay-out phase in Defined Contribution (DC) arrangements in Australia, New Zealand, and Singapore; extension of coverage of social protection schemes in China, India and Indonesia. The book also reviews social protection from a much wider perspective and extends coverage of social protection both in terms of the proportion of the population with access to the social protection scheme, and the types of risks faced by the households and by society as a whole. The East Asia experience has both implications and lessons to be learnt for the rest of the world"..